Effect of warm-up on intermittent sprint performance - Anderson, P.; Landers, G.; Wallman, K. (Research in Sports Medicine, 2014)
We aimed to investigate the effects of different warm-up (WUP) intensities on 10 min of subsequent intermittent-sprint running performance. Eleven male, team-sport players performed four trials in a randomized, cross-over design, consisting of an intermittent-sprint protocol (15 × 20-m sprints) that followed either no-WUP or one of three 10-min WUP trials that varied in intensity. Warm-up intensities were performed at either (1) half the difference between anaerobic threshold (AT) and lactate threshold (LT) [(AT-LT)/2] below the LT = WUP 1; (2) midway between LT and AT level = WUP 2; (3) [(AT-LT)/2] above AT = WUP 3. Sprint times were fastest following WUP 3, compared with all other trials, for sprints 1-9 and 14, as well as for total accumulated sprints, with these results supported by moderate to large effect size (ES; range: d = -0.50 to -1.06) and "possible" to "almost certain" benefits. Warm-up 3 resulted in faster intermittent-sprint running performance compared with lower intensity WUPs and no WUP for the first 6 min of sprinting, with accumulated sprints for the entire 10 min protocol also being faster after WUP 3. This information may be pertinent to coaches of team-sport games with respect to player substitutions.